2020
DOI: 10.1532/hsf.2861
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of del Nido Cardioplegia and Blood Cardioplegia in Aortic Root Surgery

Abstract: Aim: To compare del Nido cardioplegia (DNC) with conventional blood cardioplegia (BC) in aortic root surgery. Methods: Subjects who underwent aortic root surgery during a 3-year period were included. A DNC group was compared with a matched BC group. Results: A total of 72 subjects were included, 36 who underwent DNC compared with 36 propensity-matched subjects who underwent BC. Fifty-one (70.8%) were male, and 21 (29.2%) were female, with a mean age of 66.19 ± 7.02 years (range 51 to 81). No significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 8 publications
0
23
0
Order By: Relevance
“…Forty-one studies regarding DNC versus CC for myocardial protection used in adult cardiac surgery were included in the final analysis. 7,8,2058 On the basis of 9 retrospective observational studies we had previously included, another 32 studies published after September 2016 were included. Four of these studies were randomized controlled trials (RCTs), 24,36,39,43 one was a prospective observational study 20 while the rest were retrospective observational studies.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Forty-one studies regarding DNC versus CC for myocardial protection used in adult cardiac surgery were included in the final analysis. 7,8,2058 On the basis of 9 retrospective observational studies we had previously included, another 32 studies published after September 2016 were included. Four of these studies were randomized controlled trials (RCTs), 24,36,39,43 one was a prospective observational study 20 while the rest were retrospective observational studies.…”
Section: Resultsmentioning
confidence: 99%
“…Thirty-eight and 39 studies respectively involving 21,391 and 21,595 patients reported CPB 7,8,2031,33,3542,4458 and ACC time. 7,8,2033,3542,44…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations